Pengaruh Digital Payment Dan Self-Control Terhadap Perilaku Konsumtif Menggunakan Aplikasi Belanja Online (PT NCS Kemanggisan): The Effect of Digital Payment and Self-Control on Consumptive Behavior Using Online Shopping Applications (PT NCS Kemanggisan) - Irine Rizkyta Sari; Rani Rani (CV Warnak Johanna Nusantara, 2026)
This research was conducted at PT Nusantara Card Semesta Kemanggisan which aims to analyze the influence of digital payment (X1) and self-control (X2) on consumptive behavior (Y) in using online shopping applications. Data was collected through a survey of 72 card division employees using a questionnaire with a non-probability sampling technique using saturated samples. The method used in this study is a quantitative approach, data analysis is carried out using IBM SPSS Statistics ver software. 26.0. The results of the study concluded that: 1) Partially digital payment (X1) had a positive and significant effect on consumptive behavior (Y), as evidenced by a t-count value of 5,659 > t-table of 1.994 and a significance level of 0.000 < 0.05. 2) Self-control (X2) had a positive and partially significant effect on consumptive behavior (Y), with a t-count value of 6,920 > t-table of 1.994 and a significance of 0.000 < 0.05. 3) Digital payment (X1) and self-control (X2) together had a significant effect on consumptive behavior (Y), with an F-calculated value of 68,900 > F-table 3.13 and a significance level of 0.000 < 0.05.